2001
DOI: 10.1093/jac/48.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effects of positively charged surfaces on adhering Gram-positive and Gram-negative bacteria

Abstract: The infection of biomaterials is determined by an interplay of adhesion and surface growth of the infecting organisms. In this study, the antimicrobial effects on adhering bacteria of a positively charged poly(methacrylate) surface (xi potential +12 mV) were compared with those of negatively charged poly(methyl methacrylate) (-12 mV) and a highly negatively charged poly(methacrylate) (-18 mV) surface. Initial adhesion of Staphylococcus aureus ATCC 12600, Staphylococcus epidermidis HBH(2) 102, Escherichia coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
272
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 509 publications
(302 citation statements)
references
References 21 publications
16
272
2
1
Order By: Relevance
“…These assignments are summarized in Table 3. Bacterial adhesion to surfaces, and subsequent biofilm growth, is facilitated by biospecific (protein-protein, carbohydrate-protein) and non-specific (hydrophobic or electrostatic) surface interactions of pili and flagella [29,39].…”
Section: Resultsmentioning
confidence: 99%
“…These assignments are summarized in Table 3. Bacterial adhesion to surfaces, and subsequent biofilm growth, is facilitated by biospecific (protein-protein, carbohydrate-protein) and non-specific (hydrophobic or electrostatic) surface interactions of pili and flagella [29,39].…”
Section: Resultsmentioning
confidence: 99%
“…Cationic groups are the ones that facilitate the adsorption of antimicrobial cationic polymers to the surface of microbial membranes. There are several choices that bear the cationic centers, including ammonium ions, [14][15][16][17] sulfonium ions, 18 phosphonium ions 19,20 and so forth. This section mainly focuses on ammonium-based and iminium-based cationic groups because of their simple syntheses and broad usages.…”
Section: Monomer Designsmentioning
confidence: 99%
“…This may be due to the greater resistance of E. coli in direct contact with the edge of the GO compared with S. aureus. Although S. aureus is a Gram-positive bacteria whose peptidoglycan layer provides additional strength to the cell wall, which is also thicker (20-80 nm) than that of E. coli (Gram-negative) bacteria (7-8 nm) [9,24,25], the S. aureus was less resistant than E. coli. Gram-negative E. coli has a much thinner layer of peptidoglycan, but it also has a layer of lipopolysaccharides that might protect the cell.…”
Section: Measurements Of Bacterial Survival and Rna Leakagementioning
confidence: 99%
“…Mafu et al reported that the first and the most important such force was the electrostatic force of charges between the surface substrate and bacterial membrane [29]. They show that GO being negatively charged due to the presence of carboxyl, hydroxyl, and epoxy groups is less repulsive to Gram-positive bacteria than Gram-negative bacteria [25].…”
Section: Measurements Of Bacterial Survival and Rna Leakagementioning
confidence: 99%